Reviews and notices - Bülow-Møller, Anne Marie; Björk, Lennart; Lindquist, Hans; Shima, Allan; Trotta, Joe; Henningsson, Wendy; Neuhaus, Stefan; Neumann, Ingrid; Arvidsson, Karl-Anders; Benson, Ken (Moderna Språk, 1997)
Includes the following reviews: pp. 102-103. Anne Marie Bülow-Møller. Björk, L. & Räisänen, Ch., Academic Writing. pp. 103-105. Lennart Björk. Fjellestad, D. & Wikborg, E., Reading Texts: An Introduction to Strategies of Interpretation and Reading Texts: Teaching Suggestions. pp. 105-108. Hans Lindquist. Svartvik, J. & Sager, O., Engelsk universitetsgrammatik (med övningsbok). pp. 108-110. Allan Shima. Bennet, A. & Royle, N., An Introduction to Literature. pp. 110-112. Joe Trotta. Rothenberg, J. & Joris, P. (eds), Poems for the Millenium. p. 112. Wendy Henningsson. Lubbers, K., Born For The Shade. pp. 112-114. Stefan Neuhaus. Reimann, B. & Wolf, Ch., Sei gegrüßt und lebe. pp. 114-115. Ingrid Neumann. Opitz, S. (Hrsg.), Interkulturelle Kompetenz Skandinavien-Deutschland. pp. 116-118. Karl-Anders Arvidsson. Binon, J., Van Dyck, J., Folon, J. & Verlinde, S., Dictionnaire contextuel du français économique, tomes A-D. pp. 118-120. Ken Benson. Navajas, G., Más allá de la postmodernidad.